2020
DOI: 10.2147/ijwh.s266748
|View full text |Cite
|
Sign up to set email alerts
|

<p>Survival Time to Modern Contraceptive Uses from the Resumption of Sexual Intercourse Among Postpartum Women in Ethiopia</p>

Abstract: Background: The timing of contraceptive use is important for a woman who intends to avoid pregnancy during the postpartum period and it has key implications for reproductive health outcomes. Therefore, this study aimed to determine the time it takes to start modern contraceptive uses from the resumption of sexual intercourse among postpartum women in Ethiopia and to identify its predictors. Methods: A cross-sectional study using the 2016 Ethiopia Demographic and Health Survey (EDHS) was applied. The data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
1
7
3
Order By: Relevance
“…This finding is consistent with studies conducted in Ethiopia (59.1%) and Kenya (60.0%) ( 35 , 38 ). However, this estimate is considerably lower than other study done in Northwest Ethiopia (66.7%) ( 36 ) and higher than the nation-wide study done in Tanzania ( 37 ) and Ethiopia ( 56 ). We speculate that there may be differences in sample population characteristics, study design, and outcome variable measurement.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…This finding is consistent with studies conducted in Ethiopia (59.1%) and Kenya (60.0%) ( 35 , 38 ). However, this estimate is considerably lower than other study done in Northwest Ethiopia (66.7%) ( 36 ) and higher than the nation-wide study done in Tanzania ( 37 ) and Ethiopia ( 56 ). We speculate that there may be differences in sample population characteristics, study design, and outcome variable measurement.…”
Section: Discussioncontrasting
confidence: 70%
“…Women's place of residence and their community early marriage status were predicted time interval-to-contraceptive use after childbirth when other variables were controlled for. As in other studies ( 56 , 57 ), rural women took a long time to adopt modern methods postpartum than their counterparts. Our findings contrast somewhat with several prior studies ( 35 , 37 ) that have identified no difference in time to modern contraceptive use among rural and urban residents.…”
Section: Discussionsupporting
confidence: 60%
“…Dealing about the resumption of post-partum sexual intercourse and its determinant is especially important for giving emphasis to post-partum complications of maternal health outcomes and unintended pregnancy [18,[30][31][32]. Cultivating the culture of resumption of postpartum sexual intercourse in the recommended time is the weapon for the reduction of maternal, neonatal, and child mortality due to infection, the complications of unintended pregnancy, and the adverse consequences of short interbirth interval in Ethiopia [17,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Our study also found that only 25 (6.5%) women reported currently using contraception compared to the 100 who reported resuming sexual intercourse. This nding is supported by a study in Ethiopia among postnatal women which found a median time to start of modern contraceptive use of 4 months after resumption of sexual intercourse [23]. This highlights a delay in return to postpartum contraceptive use after resumption of sexual intercourse.…”
Section: Discussionmentioning
confidence: 60%
“…However, not much is done to align this message with the timing of sexual intercourse resumption for women in the postpartum period. As a result, we have women living with HIV who resume sexual intercourse after child birth before they return to contraceptive use [23].…”
Section: Introductionmentioning
confidence: 99%